2022
DOI: 10.3389/fpsyg.2022.886168
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Parent–Adolescent Relationship Affect Adolescent Internet Addiction? Parents’ Distinctive Influences

Abstract: Although previous research has demonstrated that parent–adolescent relationships have a significant effect on adolescent Internet Addiction (IA), the mechanisms underlying these associations and parental differences in these effects have received insufficient attention. We investigated the mediating role of Perceived Social Support and Dual System of Self-Control (DSSC) in the relationship between Father-Adolescent Relationships/Mother-Adolescent Relationships (FAR/MAR) and adolescent IA, as well as the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…For example, punitive parenting has a greater impact on adolescent problematic internet use than over-protection and rejection [35]. Some studies are focused on how different parenting styles of fathers and mothers affect adolescents' internet addiction [37][38][39]. Lansford et.al [37] showed that fathers' psychological control can affect children's developmental problems.…”
Section: Parenting Styles and Internet Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, punitive parenting has a greater impact on adolescent problematic internet use than over-protection and rejection [35]. Some studies are focused on how different parenting styles of fathers and mothers affect adolescents' internet addiction [37][38][39]. Lansford et.al [37] showed that fathers' psychological control can affect children's developmental problems.…”
Section: Parenting Styles and Internet Addictionmentioning
confidence: 99%
“…Lansford et.al [ 37 ] showed that fathers’ psychological control can affect children’s developmental problems. Another study [ 38 ] revealed that the mother-adolescent relationship is more closely linked to internet addiction than the father-adolescent relationship among adolescents. Fathers are more likely to promote teenage internet addiction with rejective and overprotective parenting styles [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents who feel more unhappiness and dissatisfaction in their childhood get more easily addicted to social media [11]. Similarly, a good mother-adolescent relationship could help adolescents' reflective system, which would benefit self-monitoring and prevent internet addiction since internet addiction includes social media addiction [12].…”
Section: Childhood and Family Boundsmentioning
confidence: 99%
“…However, unfortunately quite a lot of them, especially children do not yet understand how to use the internet well and the risks they will receive if they use the internet. So many children become victims when they are using the internet (Qi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, parents are figures or figures who have an important role and are also influential in educating, nurturing, and preventing problems related to internet use that often occur in children. Therefore, parents, especially mothers are expected to have sufficient knowledge about good internet use (Hsieh et al, 2018;Qi et al, 2022;Zhang et al, 2019). But unfortunately, until now there are still many parents who do not have enough knowledge about the internet.…”
Section: Introductionmentioning
confidence: 99%